Corporate Disclosure of Sustainability Reporting and Value Relevance in Developing Countries - A Review of Literature - Abdulkadri Toyin Alabi; Saheed Olanrewaju Issa (Universitas Airlangga, 2022)
In many countries, sustainability reporting has now become popular and necessary, as well as the impact of sustainability implementation and disclosures on firm value remains mixed. As a result, the focus of this study is primarily on the impact of sustainability reporting on the value relevance of firms in developing countries. This paper draws on arguments from a variety of theoretical frameworks; stakeholders' theory and legitimacy theory. A systematic approach was adopted in this study to form the basis for the study’s conclusion and recommendations. The results of the evaluated existing literature revealed that the influence of sustainability reporting on business value was contradictory. A vast number of studies, on the other hand, showed a favourable association between sustainability reporting and business value. Second, the research discovered that the degree of sustainability disclosure in emerging countries was lower than in other industrialized countries. It was discovered that existing research on the industry analysed and sample size utilized had certain methodological issues. This paper adds to the field by providing crucial insights into the influence of sustainability reporting on company value using samples from developing countries. As a main proposal in the report, implementing sustainability disclosure methods may increase the value relevance of firms.